Pengembangan Buku Saku IPAS Berbasis Multiple Intelligences untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Energi dan Perubahannya: Development of Multiple Intelligences-Based Science Pocket Book to Improve Students' Understanding of Energy Materials and Their Changes - Liyana Mardova; Thoha Firdaus; Sri Devi Melinda; Salysa Eka Nabila (Pendidikan Fisika Universitas Nurul Huda, 2026)
This research is motivated by the problem that students tend to have difficulty understanding physics concepts. This causes students to be less enthusiastic and their understanding of the material to be low. Therefore, innovative teaching materials are needed in the form of pocketbooks based on multiple intelligences, so that students can learn according to their potential and individual learning styles. The purpose of this study is to produce a pocketbook based on multiple intelligences that is suitable for use and to determine the improvement of students' conceptual understanding at SMK Negeri 01 Belitang Madang Raya about energy and its changes. The development of this pocketbook uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with a Likert scale to obtain results on the feasibility of the media and material. After the implementation was carried out in class X of SMK Negeri 01 Belitang Madang Raya, data from pre-tests and post-tests were obtained and analyzed using the N-Gain test. The average N-Gain score of 0.33% falls into the medium category, indicating an improvement in students' understanding after using the multiple intelligences-based pocketbook. Thus, it can be concluded that the development of a multiple intelligences-based pocketbook is considered feasible for use in physics learning and effective in enhancing students' conceptual understanding of energy and its changes